Receptor activator of NF-κB ligand promotes proliferation of a putative mammary stem cell unique to the lactating epithelium - Thomas, E.; Lee-Pullen, T.; Rigby, P.; Hartmann, P.; Xu, J.; Zeps, Nikolajs (2012)
In mice, CD49fhi mammary stem cells (MaSCs) asymmetrically divide to generate CD49f+ committed progenitor cells that differentiate into CD49f− phenotypes of the milk-secreting tissue at the onset of pregnancy. We show CD49f+ primary mammary epithelial cells (PMECs) isolated from lactating tissue uniquely respond to pregnancy-associated hormones (PAH) compared with CD49f+ cells from nonlactating tissue. Differentiation of CD49f+ PMEC in extracellular matrix produces CD49f− luminal cells to form differentiated alveoli. The PAH prolactin and placental lactogen specifically stimulate division of CD49f− luminal cells, while receptor activator of nuclear factor (NF)-κB ligand (RANKL) specifically stimulates division of basal CD49f+ cells. In nondifferentiating conditions, we observed a greater proportion of multipotent self-renewing cells, and RANKL treatment activated the RANK pathway in these cultures. Furthermore, we observed the deposition of calcium nodules in a proportion of these cells. These data imply that a MaSC unique to the lactating breast exists in humans, which generates progeny with discrete lineages and distinct response to PAH.